Nutrition for long-distance triathletes: Facts and myths - Kruseman, M.; Lecoultre, V.; Gremeaux, V. (Deutsche Zeitschrift für Sportmedizin, 2020)
Long distance triathlon (i.e. half- or full ironman distances) brings specific nutritional challenges and extra attention is necessary for optimal fueling when training six to eighteen hours weekly, especially among age-group athletes who juggle training, work and family life.